2012
DOI: 10.1371/journal.pone.0034555
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microsatellite Polymorphism in Inbred Knockout Mice

Abstract: Previously, we found that the genotype of 42 out of 198 mouse microsatellite loci, which are distributed among all chromosomes except the Y chromosome, changed from monomorphism to polymorphism (CMP) in a genetically modified inbred mouse strain. In this study, we further examined whether CMP also relates to the homologous recombination in gene knockout (KO) mouse strains. The same 42 microsatellite loci were analyzed by polymerase chain reaction (PCR) in 29 KO inbred mouse strains via short tandem sequence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
5
23
0
Order By: Relevance
“…This may be due to differences in the route and dose, and duration of E2 administration, or the effects of progesterone in mice with ovaries. MNU reportedly evokes not only various types of DNA damage [25][26][27], but also MSI and subsequent point mutations [30][31][32]. A previous study reported that an intraperitoneal injection of MNU into CD mice resulted in the development of thymic lymphoma and systemic MSI [30], suggesting that MNU impairs MMR function.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in the route and dose, and duration of E2 administration, or the effects of progesterone in mice with ovaries. MNU reportedly evokes not only various types of DNA damage [25][26][27], but also MSI and subsequent point mutations [30][31][32]. A previous study reported that an intraperitoneal injection of MNU into CD mice resulted in the development of thymic lymphoma and systemic MSI [30], suggesting that MNU impairs MMR function.…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid scaffolded assembly was polished using Quiver 10 to improve consensus accuracies in the range of Q60 and to reduce the high indel errors that are expected in the PacBio sequencing data 9 . pbalign (https://github.com/PacificBiosciences/pbalign) was used to create a bam file from all h5 files of SMRT cells and Quiver trained on P6-C4 chemistries were used to obtain the consensus corrected assembly.…”
Section: Polishing and Assembly Evaluationmentioning
confidence: 99%
“…Primers were fluorescently labeled with 6-FAM (blue), HEX (green) and TAMRA (yellow), for which the internal size standard was ROX (red). The PCR procedure was carried out as previously described (Zuo et al, 2012). Briefly, primers were first tagged to dyes at the 5' ends and PCR performed using 15 μL volume reactions.…”
Section: Stage Three: Capillary Electrophoresis-based Screeningmentioning
confidence: 99%